Immigration, différence et intégration dans The Consul et The Saint of Bleecker Street de Gian Carlo Menotti - Walter Zidaric (Revue LISA)
Composer, librettist and stage director Gian Carlo Menotti has changed the American musical theatre by accepting to face burning questions related to his times, but which are at the same time universal. In The Consul (1950), the American context of the 1950s burst onto the operatic stage. The Mc Carron law and MacCarthysm are reflected in this opera which is, first of all, a metaphor of the negation of liberty. In The Saint ofBleecker Street (1954), the Little Italy microcosm suggests a new reflection about questions which are related to the concept of difference and integration, connected to considerations of a metaphysical and religious nature. As metaphors of American society, these two operas finally symbolise all kinds of human multicultural societies by revealing the polysemic character of Menotti’s works.